2018
DOI: 10.1371/journal.pone.0197968
|View full text |Cite
|
Sign up to set email alerts
|

Negative mood invites psychotic false perception in dementia

Abstract: BackgroundThere is increasing evidence for predictive coding theories of psychosis, which state that hallucinations arise from abnormal perceptual priors or biases. However, psychological processes that foster abnormal priors/biases in patients suffering hallucinations have been largely unexplored. The widely recognized relationship between affective disorders and psychosis suggests a role for mood and emotion.MethodsThirty-six patients with dementia with Lewy bodies (DLB), a representative condition associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…In patients who demonstrate pareidolic misperceptions, we found that: (i) the pre-stimulus low-alpha power tends to be higher in Face detection on the NPT necessitates an active search-and-detect effort requiring configural face processing and a top-down integration of facial features (Revankar et al, 2020). While these images serve as sensory deprived ambiguous stimuli, a subset of PD patients consciously misperceive noisy patches as faces, likely due to abnormal perceptual biases (Watanabe et al, 2018). In our experiment during the pre-stimulus phase, this misrepresentation was observed as a near-significant increase in low-alpha spectral power in the frontal electrodes.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In patients who demonstrate pareidolic misperceptions, we found that: (i) the pre-stimulus low-alpha power tends to be higher in Face detection on the NPT necessitates an active search-and-detect effort requiring configural face processing and a top-down integration of facial features (Revankar et al, 2020). While these images serve as sensory deprived ambiguous stimuli, a subset of PD patients consciously misperceive noisy patches as faces, likely due to abnormal perceptual biases (Watanabe et al, 2018). In our experiment during the pre-stimulus phase, this misrepresentation was observed as a near-significant increase in low-alpha spectral power in the frontal electrodes.…”
Section: Discussionmentioning
confidence: 91%
“…Participants verbally responded to each image within 30s of stimulus presentation and the experimenter recorded the responses since patients' tremor severity may have prevented reliable manual responses. Visual misperceptual phenomena are strongly influenced by time of the day ('sundowning'), age-related vision problems and mood that fluctuate during the day (Suzuki et al, 2011;Weil et al, 2016;ffytche et al, 2017;Watanabe et al, 2018). To minimize these effects, we performed the NPT (i) on a fixed time of the day (late afternoons), (ii) when vision was normal or corrected-to-normal; and…”
Section: General Information and Recording Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Face detection on the NPT necessitates an active search-and-detect effort requiring configural face processing and a top-down integration of facial features(10). While these images serve as sensory deprived ambiguous stimuli, a subset of PD patients consciously misperceive noisy patches as faces, likely due to abnormal perceptual biases(13). In our experiment during the pre-stimulus phase, this misrepresentation was observed as a near-significant increase in low-alpha spectral power in the frontal electrodes.…”
Section: Discussionmentioning
confidence: 99%